126 Antioxidant-Containing Kibble Supplemented to Adult Cats Elicited Improvements in Antioxidant Outcomes and C-Reactive Protein. (21st September 2022) - Panasevich, Matthew; Daristotle, Leighann; Lin, Ching-Yen; Frantz, Nolan
Abstract: The objective of this study was to evaluate oxidative health biomarkers in healthy male and female adult cats (n=30; 10 male and 20 female, avg age and BW + SD 3.34 ± 3.19 years; 3.85 ± 1.07 kg) fed an adult maintenance diet (Blue Buffalo Healthy Living Adult Chicken and Brown Rice) without (control diet) and supplemented with an antioxidant-containing kibble (test diet; proprietary blend containing blueberries, cranberries, and other antioxidant-containing ingredients). Both diets analyzed as 35.9% crude protein, 19.8% fat, 2.1% crude fiber, 6.4% moisture, 28.6% carbohydrate as-is. We hypothesized that test feeding would reduce serum pro-oxidative biomarkers, compared with control feeding. The study protocol was first approved by the Institutional Animal Care and Use Committee. All cats were fed a base kennel maintenance diet (no added antioxidants beyond maintenance requirements) for 14d before treatment phase. Animals were then randomized to control or test for a 28d treatment period in a randomized cross-over design. Base kennel maintenance diet was provided for a 14d washout, followed by another treatment period. Serum was collected on days 0, 14, and 28 of for biomarkers analysis. Data were analyzed as a mixed models 2-way ANCOVA (SAS v9.4). Significant differences between treatments were set at P<0.05. Average daily food intake and body weight were similar between treatments for the duration of the study. Serum advanced glycation end-products and malondialdehyde were significantly (P<0.05) less when animals consumed test diet compared with control diet. Interestingly, serum C-reactive protein (CRP) was decreased and Fms-related tyrosine kinase 3 ligand was greater (P<0.05) when cats were fed test diet compared with control diet. These data suggest that inclusion of an antioxidant-containing kibble extruded to preserve antioxidant activity to a base kibble exhibits some favorable modulation to serum antioxidant markers and CRP in cats. These observations warrant additional research to elucidate the effects.